(untitled) (KYAMC Journal, 2013)
Sinus histiocytosis with lymphadenopathy is a rare condition of unknown etiology that is characterized by the overproduction of histiocytes accumulating in the lymph node sinuses and in the lymphatics of extranodal sites if involved. Lymph nodes of the neck are the most common place of histiocyte accumulation, although other lymph nodes and organs may involve, as well. The common sites of the disease outside the lymph nodes are skin, soft tissues, upper respiratory tract, the sinuses, kidney, thyroid, small bowel, breast, and bone. Hepatosplenomegaly is uncommon. The symptoms of this disease vary with the site of involvement. It is often referred to as sinus histiocytosis with massive lymphadenopathy (SHML). In this article an adult male of 38 years, has been described who presented with bilateral cervical and axillary lymphadenopathy clinically suspected of infectious (tubercular-in the context of our country) or hematological malignant etiology. However on fine needle aspiration cytology, the smears showed many histiocytes, lymphocytes and plasma cells. Biopsy of cervical lymph node showed dilated sinuses filled with histiocytes and lymph node architecture showing inflammatory cells having lymphocytes and histiocytes. These findings were considered consistent with sinus histiocytosis with chronic lymphadenitis. DOI: http://dx.doi.org/10.3329/kyamcj.v2i2.13266 KYAMC Journal Vol.2(2) January 2012, 205-208